1992
DOI: 10.1007/bf03190152
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long-term occupational exposure to carbon disulphide on serum lipids

Abstract: No definite conclusion can be made from many epidemiological and clinical studies of lipid metabolism in workers exposed to carbon disulphide (CS2). The aim of our investigation was to study the serum lipid levels in workers exposed to different CS2 levels to establish possible exposure-response relationships. The first group, spinners, were exposed to high CS2 levels; the second group, workers in viscose production, to low CS2 levels; and the third group included non-exposed workers. As a part of a large exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In addition, increased prevalence of hypertension was observed in subjects exposed to CS 2 for longer than 10 years (Balcarova and Halik 1991, Beauchamp et al 1983, Liss and Finkelstein 1996, Nofer et al 1961, Nurminen et al 1982, Peplonska et al 1996, 2001Swaen et al 1994, Sweetnam et al 1987, Tiller et al 1968, Tolonen et al 1975, Wronska-Nofer et al 1990). The increased CHD incidence related to the prolonged exposure to CS 2 was accompanied by a dyslipoproteinemia with increased total cholesterol, LDL-cholesterol, triglycerides and decreased HDL-cholesterol (Manu et al 1972, Wronska-Nofer et al 1990, Rudkowska et al 1978, Egeland et al 1992, Krstev et al 1992, Vanhoorne et al 1992. In experimental animals CS 2 was shown to induce disturbances in cholesterol synthesis and elimination of the products of cholesterol metabolism with bile (Wronska- Nofer 1969, WronskaNofer and Parke 1978, Wronska-Nofer et al 1980).…”
Section: Introductionmentioning
confidence: 93%
“…In addition, increased prevalence of hypertension was observed in subjects exposed to CS 2 for longer than 10 years (Balcarova and Halik 1991, Beauchamp et al 1983, Liss and Finkelstein 1996, Nofer et al 1961, Nurminen et al 1982, Peplonska et al 1996, 2001Swaen et al 1994, Sweetnam et al 1987, Tiller et al 1968, Tolonen et al 1975, Wronska-Nofer et al 1990). The increased CHD incidence related to the prolonged exposure to CS 2 was accompanied by a dyslipoproteinemia with increased total cholesterol, LDL-cholesterol, triglycerides and decreased HDL-cholesterol (Manu et al 1972, Wronska-Nofer et al 1990, Rudkowska et al 1978, Egeland et al 1992, Krstev et al 1992, Vanhoorne et al 1992. In experimental animals CS 2 was shown to induce disturbances in cholesterol synthesis and elimination of the products of cholesterol metabolism with bile (Wronska- Nofer 1969, WronskaNofer and Parke 1978, Wronska-Nofer et al 1980).…”
Section: Introductionmentioning
confidence: 93%
“…Half of the studies of the cardiac effects of CS 2 exposure levels ‡20 ppm are characterized by a lack of assessment or control of confounding factors, with data on potential covariates collected but only unadjusted results presented [14,24,50,56,57]. Two studies may have introduced bias due to design flaws [46,55], and one presented results that were uninterpretable with respect to the relationship between the outcomes reported and their impact on actual cardiac risk status [17].…”
Section: Cardiac Risk Indicators and High Exposures To Carbon Disulfidementioning
confidence: 98%
“…Ten of these papers, representing six specific cohorts from Finland, Japan, Belgium, Egypt, Yugoslavia and Taiwan, reported on viscose rayon workers from factories where average exposures were ‡20 ppm [14,17,24,25,46,50,55,56,57,60]. One of these, the report by Sakurai, did not include quantitative exposure estimates for the facility under study, but the author suggested that, due to lack of engineering controls in the facility under investigation, average exposure levels were likely to have exceeded 20 ppm [46].…”
Section: Cardiac Risk Indicators and High Exposures To Carbon Disulfidementioning
confidence: 99%